A Mediating Role of Adaptive Selling Behavior: Relationship between Emotional Intelligence and Sales Performance.Beverage Industry of Pakistan - Tahir Anees, Rao; Raju, Valliappan; Anjum, Tamoor (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to investigate the mediating role of adaptive sales behavior to improve emotional intelligence and sales performance within the beverage industry.The population of this research comprised ofthe Beverage Industry of Pakistan. One hundred eighty employees were selected as the sample from the two big beverage companies in Pakistan. For this research, stratified random sampling technique were used. This study uses a cross-sectional and quantitative research design based on survey methods. The questionnaire has three parts and is used for data collection. Smart PLS-3 was used to evaluate the hypothesis of this study. The Results of this study highlighted the significance mediating the role of adaptive selling behaviorto enhance emotional intelligence and sales performance. In contrast,emotional intelligence and sales performancehave a significant correlation between each other.